Last Planner System (LPS) Implementation on Jakarta-Cikampek II Elevated Toll Road Project - Ni'mah Tozahro; Afrizal Nursin (Applied Research on Civil Engineering and Environment (ARCEE), 2020)
In construction industry, its implementation of the construction has its own constraints. A good management or project management system is needed to minimize the risk of these constraints. The latest project management concept that has proven more effective and efficient is Last Planner System method. This study aims to investigate how the implementation of Last Planner System works on Jakarta-Cikampek II Elevated Toll Road Project. With the evaluation of weekly job evaluations using PPC (Percent Plan Completed) and Pareto Variance Constraint analysis, the constraint issues of this project will be identified. Then they are followed up to find the right solution in handling the constraints. The research method is done by conducting literature study, problem formulation, followed by implementing LPS method, which is through work flow control such as phase and pull plan, lookahead plan, constrain analysis, daily huddles, PPC (Percent Plan Completed) calculation, Pareto Chart analysis with data variation of issues that have been obtained. The results show that the average PPC weekly project is 83.04% and the most influential reason that must be concerned its priority is submittals.